MASHARIF AL-ZAKAT: THE HADITH MAUDHU’I APPROACH - Santoso, Ivan Rahmat; Ahmad, La Ode Ismail; Hasan, Muhammad; Aziz, Indrawan; Bachtiar, Muhammad Harsya (Jurnal Diskursus Islam, 2021)
The distribution of zakat (masharif al-zaká) is an important factor as an indicator of the optimal function of zakat. In addition to the qur’an, the zakat distribution mechanism should be based on valid traditions as references in its management. This study aims to analyze the distribution of zakat in the review of maudhu’iy hadith. The method used is a thematic approach (al-hadith al-maudhu’i). The result of the research shows that the hadith that is being discussed is categorized as hasan lighairihi hadith, where the origin is dha’if but has reinforcement from other lines so that it is elevated to hasan lighairihi. In addition, the contents of the prophet’s hadiths regarding mashârif al-zakât which are discussed do not contradict the verses of the qur’an, because they have the same meaning regarding the eight asnaf who are entitled to receive zakat.